Xylem safety in relation to the stringency of plant water potential regulation of European beech, Norway spruce, and Douglas-fir trees during severe drought - Katja Schumann; Bernhard Schuldt; Miriam Fischer; Christian Ammer; Christoph Leuschner (Trees, 2024)
Key message Norway spruce operates with larger hydraulic safety margins (HSM) than beech and Douglas-fir despite the known drought sensitivity of spruce, questioning a pivotal role of HSM in drought tolerance. Abstract The exceptional 2018/2019 drought exposed Central Europe’s forests to severe stress, highlighting the need to better understand stomatal regulation strategies and their relationship to xylem safety under extreme drought. We studied diurnal, seasonal, and inter-annual variation in stomatal conductance ( g s ) and leaf water potential ( Ψ Leaf ) in co-occurring European beech ( F. sylvatica ), Norway spruce ( P. abies ), and Douglas-fir ( P. menziesii ) trees in the two summers and related them to hydraulic traits characterizing drought resistance. In 2018, F. sylvatica exhibited a continuous Ψ Leaf decline from June to September, as is characteristic for an anisohydric strategy, while P. abies closed stomata early and reached the least negative Ψ Leaf -values at the end of summer. P. menziesii showed low Ψ Leaf -values close to P 12 (the xylem pressure at onset of embolism) already in July. Both conifers closed stomata when approaching P 12 and maintained low g s -levels throughout summer, indicative for isohydric regulation. In 2019, all three species showed a linear decline in Ψ Leaf , but F. sylvatica crossed P 12 in contrast to the conifers. The three species exhibited similar water potentials at turgor loss point (− 2.44 to − 2.51 MPa) and branch P 50 (xylem pressure at 50% loss of hydraulic conductance; − 3.3 to − 3.8 MPa). Yet, F. sylvatica and P. menziesii operated with smaller hydraulic safety margins (HSM means: 0.79 and 0.77 MPa) than P. abies (1.28 MPa). F. sylvatica reduced leaf size and specific leaf area in 2019 and increased Huber value. Our species comparison during extreme drought contradicts the general assumption that conifers operate with larger HSMs than angiosperm trees. Contrary to expectation, P. abies appeared as hydraulically less vulnerable than Douglas-fir.